2020
DOI: 10.1002/ptr.6565
|View full text |Cite
|
Sign up to set email alerts
|

Antiinflammatory and anti‐cancer activities of pomegranate and its constituent, ellagic acid: Evidence from cellular, animal, and clinical studies

Abstract: Inflammation is commonly characterized as a defensive and protective reaction of the body to various exogenous or endogenous stimuli, which aims to maintain the body health. Punica granatum (pomegranate) and its constituent ellagic acid (EA) are recently more taken into accounts since their promising pharmacological effects. Therefore, we aimed to obtain a comprehensive review regarding antiinflammatory, anticancer, and antioxidant activities of both pomegranate and EA and their possible involved mechanisms. I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
72
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 133 publications
(89 citation statements)
references
References 199 publications
(305 reference statements)
0
72
0
Order By: Relevance
“…Among diverse compounds, ellagic acid has been identified as one of the main components of Chinese wild raspberry extract and is associated with various biological activities [30]. Indeed, ellagic acid has reported to have immunoregulatory function and anti-cancer capacity for the prevention of several cancers [31]. Ellagic acid regulates LPS-induced maturation of bone marrow-derived dendritic cells (BMDCs) by the modulation of c-Jun N-terminal kinase (JNK) activity [32].…”
Section: Discussionmentioning
confidence: 99%
“…Among diverse compounds, ellagic acid has been identified as one of the main components of Chinese wild raspberry extract and is associated with various biological activities [30]. Indeed, ellagic acid has reported to have immunoregulatory function and anti-cancer capacity for the prevention of several cancers [31]. Ellagic acid regulates LPS-induced maturation of bone marrow-derived dendritic cells (BMDCs) by the modulation of c-Jun N-terminal kinase (JNK) activity [32].…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that EA has antiproliferative and antioxidant properties, which is found in many vegetables, fruits and nuts, such as pomegranates, strawberries, raspberries, and so forth. 13 And many experimental evidences showed that EA displayed significant antitumor, antiangiogenic, and antimetastatic activities. 14 The anticarcinogenic effect of EA has been shown in some types of tumors, including prostate cancer, lung cancer, osteosarcoma, breast cancer, and so forth.…”
Section: Discussionmentioning
confidence: 99%
“…EA is a chromene-dione derivative (2,3,7,8-tetrahydroxy-chromeno [5,4,3-cde]chromene-5,10dione), encompassing both a hydrophilic moiety with 4 hydroxyl groups and 2 lactone groups, and a planar lipophilic moiety with 2 biphenyl rings. This particular structure has both hydrogenbonding acceptor (lactone) and donor (−OH) sites ( Figure 1).…”
Section: Ea Chemical Structure and Solubilitymentioning
confidence: 99%
“…Present also in a large variety of tropical fruits, nuts, berries (strawberries, raspberries, blackberries, cranberries, goji berries) and in a type of edible mushroom (Fistulina epatica), EA has recently attracted deep interest, since many research studies evidenced the role of oxidative stress in different pathologic conditions like cancer, diabetes, cardiovascular and autoimmune diseases, obesity and neurodegenerative disorders [2][3][4][5][6][7]. In this regard, EA may be a useful adjunct in Parkinson's disease treatment, as it proved to protect dopamine from oxidation and, by reducing inflammation and oxidative stress, to exert a neuroprotective effect [8].…”
mentioning
confidence: 99%